Dampak Algorithmic Management Terhadap Profitabilitas dan Resiliensi Ekonomi UMKM pada Platform Food Delivery di Kota Metro - Ilham Setio Wibowo; Robi Santoso; Tiara Anggia Dewi (Indo Publishing, 2026)
Due to digital transformation, MSMEs prefer to use food delivery platforms as a way to enhance their business outcomes and sustainability. Data-driven management systems are used by these platforms to control product visibility, order distribution, and data-based promotions. This study uses a quantitative approach to analyze the impact of algorithmic management on the profitability and economic resilience of MSMEs listed on food delivery platforms in Metro City. 30 MSMEs listed on the platform were surveyed in this research. The analysis was conducted using multiple linear regression. With a regression coefficient of 0.438 and a significance level of 0.000 (p < 0.05), the research results indicate that algorithmic management has a positive and significant effect on the profitability of SMEs. With a regression coefficient of 0.512 and a significance level of 0.000 (p < 0.05), algorithmic management also has a positive and significant impact on the economic resilience of SMEs. These results show that algorithmic systems enhance operational efficiency, improve market access, and help businesses adapt to changes in the business environment. This study provides a theoretical contribution to the development of literature on digital economy and entrepreneurship. It also offers practical implications for SMEs and policymakers in supporting the digital transformation of SMEs.